Microstructure and Selected Properties of Si3N4 + SiC Composite - Gábrišová, Zuzana; Švec, Pavol; Brusilová, Alena (Manufacturing Technology Journal, 2020)
The effects of strengthening phase in particulate ceramic composites on their properties were studied in presented paper. The experimental materials were a monolithic Si3N4 and particulate ceramic composites consisting of Si3N4 matrix with different additions of the SiC strengthening phase (10 and 20 vol.%). The microstructure, density, hardness and fracture toughness of Si3N4 + SiC ceramic composite materials were compared with monolithic Si3N4 based ceramic material. The addition of SiC particles into the Si3N4 based matrix does not positively influence the phase transformation from ?-Si3N4 to ?-Si3N4 in Si3N4 + SiC ceramic composite materials, but it affects the growth of prismatic ?-Si3N4 grains and contributes to the creation of fine-grained microstructure. The increase of SiC strengthening phase portion slightly increases relative density of Si3N4 + SiC ceramic composite materials. The hardness of ceramic materials increased from 14.48 GPa at monolithic Si3N4 ceramics to 16.99 GPa at ceramic composite with 20 vol.% SiC. The highest fracture toughness value of 8.30 MPa.m1/2 was achieved for monolithic Si3N4 ceramics, the lowest value of 7.09 MPa.m1/2 was achieved for ceramic composite with 20 vol.% SiC.
Keywords: silicon nitride; strengthening phase; microstructure; mechanical properties